2016
DOI: 10.1007/s11230-016-9638-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of three avian haemoproteids (Haemosporida, Haemoproteidae), with the description of Haemoproteus (Parahaemoproteus) palloris n. sp.

Abstract: DNA barcoding (molecular characterisation) is a useful tool for describing the taxonomy and systematics of organisms. Over 250 species of avian haemosporidian parasites have been described using morphological characters, yet molecular techniques based on polymerase chain reaction (PCR) suggest this diversity is underestimated. Moreover, molecular techniques are particularly useful for the detection of chronic infections and tissue stages of these parasites. Species delimitation is problematic among haemosporid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
1
20
0
1
Order By: Relevance
“…species was accompanied by DNA sequence information and phylogenetic hypothesis for its relationship with already described parasites. It has been suggested [ 60 ] and then confirmed by several other studies [ 15 , 58 , 61 ] that Haemoproteus lineages, which differ over 5% in partial cytb sequence (479 bp), are likely to be morphologically differentiated and can be distinguished on gametocyte stage. However, it was also shown that some cytb lineages of Haemoproteus spp.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…species was accompanied by DNA sequence information and phylogenetic hypothesis for its relationship with already described parasites. It has been suggested [ 60 ] and then confirmed by several other studies [ 15 , 58 , 61 ] that Haemoproteus lineages, which differ over 5% in partial cytb sequence (479 bp), are likely to be morphologically differentiated and can be distinguished on gametocyte stage. However, it was also shown that some cytb lineages of Haemoproteus spp.…”
Section: Discussionmentioning
confidence: 82%
“…In H. palloris (Fig. 1o ), an unfilled space is usually present between the gametocyte and the erythrocyte nucleus [ 15 ]. This is not characteristic for H. homopalloris n. sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 150 species of avian haemoproteids (Haemoproteidae) belonging to the genus Haemoproteus (subgenera Haemoproteus and Parahaemoproteus ) have been described [4, 18, 144], and recent molecular studies indicate that many more species probably exist [17]. However, there is, at best, only fragmentary information on exo-erythrocytic development in the great majority of the species (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Migration distance may vary substantially across the study population, given that individuals may breed at different distances from the Zambian winter site. Two lineages of malaria-like parasites (WW1 and WW2), belonging to the morphospecies Haemoproteus palloris (Dimitrov et al, 2016) and H. majoris (Križanauskienė et al, 2006), respectively, have previously been recorded as the dominant haemosporidian parasites in willow warblers (WW1 and WW2; Bensch & Akesson, 2003).…”
Section: Introductionmentioning
confidence: 99%